First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations Resolutions and Petitions The League was a signatory to resolutions and petitions to Government relating to The Educational Food and Health Campaign, Pure Food Society, Women Police, The Criminal Law Amendment Bill. The League was invited to nominate a delegate to the deputation which waited on the Minister of Health from the Coal Smoke Abatement Society. Dr. C.W. Saleeby, Member of the Medical Council of the League being nominated to represent the League. We have found that the organisations dealing with the female population of the country, which in certain cases are even represented upon the Lay Council of the League, have been slow to avail themselves of the opportunity for receiving health instruction from the lecturing staff of the League, while the organisations dealing with the male population, on the contrary, have arranged for lectures which have been attended in large numbers. Maternity Homes. The Medical Council of the League, in November, 1919, pointed out the great need for increased Maternity Homes in this country, and further suggested that part of the money raised for War Memorials should be allocated to the foundations of Maternity Homes. Labour Federations and Trades Unions. It is hoped that the League will become the official Educational Health League of the Labour Federations and Trades Unions of the country. We are supported and Unions. recommended by the Rt. Hon. J.R. Clynes, M.P., and Mr. C.W. Bowerman, M.P., Lay Councillors of the League. The Church's Interest. We have approached the Archbishops, Bishops, Roman Catholic Archbishops and Bishops, and Nonconformist Ministers of the country, inviting their sympathy and help in the work of the League, and have received sympathetic replies from the Archbishop of Canterbury, the Bishop of Oxford, the Bishop of Liverpool, the Bishop of Salisbury, and the Bishop of Birmingham is not only a Vice-President of the League, but is also a very active member of its Lay Council. We are hoping to be supported in our work by an annual Sunday Collection in the Churches of each diocese. Through the Medical Officer of Health for Glasgow, Dr. A.K. Chalmers, the League has been brought to the notice of the Moderators of the Churches of Scotland. The Established Church and the United Free Church, and both the Moderators, the Rev. Thomas Martin and the Rev. J. McClymont, have expressed their willingness to help the work in Scotland, indeed, to give their whole-hearted support to the movement, and have suggested that a public meeting should be held ; this we have not yet been able to arrange. Private Appeals. We have also approached the following Associations, Institutes and Trusts, for grants to carry on the educational work of the League, so far without any favourable response. A further appeal will be made during the coming year, when it is hoped we shall be more successful. The British Red Cross Association, through our Lay Councillor, the Hon. Sir Arthur Stanley, G.B.E., C.B., M.V.O. The Queen Alexandra Rose Day Fund. United Services Fund. The L.C.C. (Cinema Sunday Performances), through our Lay Councillor, Dr. Kimmins, late Chief L.C.C. Inspector. The Rockfeller Foundation Trust, introduced through the kindness of the late General W.G. Gorgas. The Carnegie Trust, introduced by our Medical Councillor, Dr. Edward Hope, M.O.H., Liverpool. We also have approached the City Companies and Insurance Companies and Approved Societies, but with the exception of the London 36 200/B/3/2/C693/1/71